Application of cryopreservation to tooth germ transplantation for root development and tooth eruption - Xinghan Li (Nature Portfolio, 2021)
Abstract We cryopreserved mouse tooth germs with widely open cervical margins of the enamel organ to overcome difficulties in cryoprotectant permeation and tested their efficacy by transplanting them into recipient mice. The upper right first molar germs of 8-day-old donor mice were extracted and categorized into the following four groups according to cryopreservation time: no cryopreservation, 1 week, 1 month, and 3 months. The donor tooth germs were transplanted into the upper right first molar germ sockets of the 8-day-old recipient mice. The upper left first molars of the recipient mice were used as controls. The outcome of the transplantation was assessed at 1, 2, and 3 weeks after transplantation. Stereomicroscopic evaluation revealed that most of the transplanted teeth erupted by 3 weeks after transplantation. Micro-computed tomography analysis revealed root elongation in the transplanted groups as well as in the controls. There was no significant difference between the cryopreserved and non-cryopreserved transplanted teeth, but the roots of the cryopreserved teeth were significantly shorter than those of the control teeth. Histological examination revealed root and periodontal ligament formations in all the transplanted groups. These results suggest that the transplantation of cryopreserved tooth germs facilitates subsequent root elongation and tooth eruption.